2016
DOI: 10.1016/j.jcis.2016.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of T4 bacteriophages on planar indium tin oxide surface via controlled surface tailoring

Abstract: The work investigates the influence of surface physicochemical properties of planar indium tin oxide (ITO) as a model substrate on T4 bacteriophage adsorption. A comparative T4 bacteriophage adsorption study shows a significant difference in bacteriophage adsorption observed on chemically modified planar ITO when compared to similarly modified particulate ITO, which infers that trends observed in virus-particle interaction studies are not necessarily transferrable to predict virus-planar surface adsorption beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The phage density on MUA treated gold surface was comparable to gold and APTES-coated silicon. A previous study found fewer attached phages on the APTES treated ITO-surface compared to the carboxylate-treated one, 20 suggesting planar surfaces have distinct adsorption dynamics compared to particulate surfaces, for which amine treatment resulted in strong adsorption. 32,33 This suggestion was not confirmed by our study.…”
Section: Attached Phagesmentioning
confidence: 94%
See 1 more Smart Citation
“…The phage density on MUA treated gold surface was comparable to gold and APTES-coated silicon. A previous study found fewer attached phages on the APTES treated ITO-surface compared to the carboxylate-treated one, 20 suggesting planar surfaces have distinct adsorption dynamics compared to particulate surfaces, for which amine treatment resulted in strong adsorption. 32,33 This suggestion was not confirmed by our study.…”
Section: Attached Phagesmentioning
confidence: 94%
“…To clarify the mechanisms involved with antimicrobial effects of immobilized phages, we studied the phage attachment density, the detachment rate, and the infectivity of surface-immobilized Flavobacterium -infecting bacteriophages on five different surfaces: silicon, amine-treated silicon, gold, carboxylate-treated gold, and cross-linker-activated carboxylate-treated gold. These specific surfaces were selected because they have been used in the previous immobilization studies and are known to result in different surface densities of phages. , To understand whether the antibacterial effect of these surfaces is caused by the attached or the detached phages, the strength of the immobilization was also analyzed by 3–12 washing steps. The amine-treated silicon surface generated a high release of phages and maintained the highest infectivity, even after extensive washing, suggesting that detached phages are important.…”
Section: Introductionmentioning
confidence: 99%
“…For immobilization on silicate-based materials, a preferred method is silanization of the substrate using alkoxysilanes which act as hetero-bifunctional crosslinkers between inorganic mineral surfaces and organic ligands 37,50,51,60,62,67,79,80,95,141,142,[144][145][146]173,174 .…”
Section: Silane-based Self-assembled Monolayersmentioning
confidence: 99%
“…Recently, Imai et al [46] claimed to utilize core−shell nanoparticles with the surface charge to orient phages S13 properly. Results reported by Liana et al [58] suggest that there is another layer of complexity in such a seemingly simple system. The authors compared amino-(positive charge in neutral pH) and carboxylic-(negative charge in neutral pH) functionalized surfaces of indium tin oxide (ITO).…”
Section: Oriented Layers Of Bacteriophagesmentioning
confidence: 94%
“…It was found that more T4 virions were adsorbed on negatively charged planar ITO, whereas in the case of particulate ITO, better coverage was achieved for positively charged particles. The authors explained it in terms of variations of time available to bind phages on planar (longer time required) versus particulate (shorter search time) ITO [58]. Anyhow, Bone et al [59], again proved that chemisorption allowed for much higher surface coverages.…”
Section: Oriented Layers Of Bacteriophagesmentioning
confidence: 99%